1992
DOI: 10.1115/1.2929189
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Simulated Rotation on Tip Leakage in a Planar Cascade of Turbine Blades: Part I—Tip Gap Flow

Abstract: The paper presents further results from a continuing study on tip leakage in axial turbines. Rotation has been simulated in a linear cascade test section by using a moving-belt tip wall. Measurements were made inside the tip gap with a three-hole pressure probe for a clearance size of 3.8 percent of the blade chord. Two wall speeds are considered and the results are compared with the case of no rotation. As in other experiments, significant reduction in the gap mass flow rate is observed due to the relative mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…The chordwise velocity vector distributions at different spanwise distance within the tip gap were studied by Yaras and Sjolander. 39 They found that apart from the areas very close to the leading edge and trailing edge, the tip leakage flow crossed the tip perpendicular to the chord. Hence it was concluded that the flow momentum mainly changed in the direction normal to the chord.…”
Section: Methodsmentioning
confidence: 99%
“…The chordwise velocity vector distributions at different spanwise distance within the tip gap were studied by Yaras and Sjolander. 39 They found that apart from the areas very close to the leading edge and trailing edge, the tip leakage flow crossed the tip perpendicular to the chord. Hence it was concluded that the flow momentum mainly changed in the direction normal to the chord.…”
Section: Methodsmentioning
confidence: 99%
“…One of the reasons for the different behaviour of tip leakage flows in linear cascades and rotors is due to the omission of end wall motion. Though the literature is not exhaustive few investigators have studied the effect of wall motion on the tip gap aerodynamics (Graham, et al [7], Morphis and Bindon [8], Yaras and Sjolander [9]). Substantial decrease in the gap flow rate as a result of the wall motion is reported by Yaras and Sjolander [9] and Krishnababu and Whitney [10].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of relative motion had been investigated by Morphis and Bindon 13 and Yaras and Sjolander. 14 In their major studies, shear effects (or scraping flow) would presumably become more important at small clearances. The countereffect of the scraping flow reduces the leakage, whereas the flow pattern at the clearance has not been affected by it greatly.…”
Section: Introductionmentioning
confidence: 99%